Computational-experimental strategy identifies Co-upregulated biomarkers linking coronary heart disease and type 2 diabetes pathogenesis - Li, Wei; Cao, Yu; Yu, Chen; Che, Bingjun; He, Miao; Li, Dongbiao; Jiang, Lihong; Ma, Lijing (Frontiers in Genetics, 2025)
BackgroundCoronary heart disease (CHD) and type 2 diabetes (T2D) represent a significant global comorbidity burden, with shared yet incompletely understood molecular mechanisms. This study aimed to identify shared diagnostic biomarkers and elucidate core pathways linking CHD and T2D pathogenesis.MethodsIntegrated bioinformatics of CHD/T2D transcriptomes identified shared differentially expressed genes (DEGs) and co-expression modules via Weighted Gene Co-expression Network Analysis (WGCNA). Receiver operating characteristic (ROC) analysis selected CPD, GGCT, SUZ12, and ZMYM2 as top diagnostic biomarkers. These predictions were validated using C57BL/6 and ApoE−/− mouse models of T2D/CHD. Aortic tissues underwent histopathology (Hematoxylin and Eosin (H&E), Oil Red O, Sirius Red) and multi-level molecular assays (immunofluorescence, Western blot, reverse transcription quantitative polymerase chain reaction (RT-qPCR).ResultsBioinformatics revealed 328 shared DEGs, with CPD, GGCT, SUZ12, and ZMYM2 showing high diagnostic efficacy. T2D mice exhibited persistent hyperglycemia. Aortic histopathology confirmed disease-specific changes: atherosclerotic plaques in CHD and vascular basement membrane thickening in T2D. Critically, all four biomarkers showed concurrent upregulation in diseased vessels at both protein (immunofluorescence, Western blot) and mRNA (RT-qPCR) levels.ConclusionThis study establishes CPD, GGCT, SUZ12, and ZMYM2 as shared CHD/T2D diagnostic biomarkers. Their validated co-upregulation highlights their dual-disease diagnostic and therapeutic potential.